Comparison between surface irrigation and drip irrigation in some productivity indicators of tomato crop in protected cultivation (Damascus University Journal of agriculture sciences, 2024)
The research was carried out at Alsanobar Research Station – Lattakia – General Commission for Scientific Agricultural Research. During the two seasons 2020–2021 to determine the effect of two different irrigation methods on the consumption of the tomato crop (Lycopersicom esculentum) and some studied indicators.Two irrigation treatments (surface irrigation, drip irrigation) in Three replications by using full random sectors.The water consumption of the crop was calculated and the effect of irrigation method on (productivity, plant height, maximum flowering date) was studied.The total water consumption was determined as 5531.4 m3/ha for the surface irrigation treatment, and 3872 m3/ha for the drip irrigation treatment by saving 30% of the water provided in the surface irrigation treatment.Drip irrigation was superior in terms of plant height, early flowering, and the average productivity of the greenhouse 2.72 tons/house by 51.2%, compared with surface irrigation.
Keywords: Surface Irrigation; Drip Irrigation; Tomatoes; Productivity; Water Consumption